Tribological investigations on the application of oil-miscible ionic liquids additives in modified Jatropha-based metalworking fluid - Amiril, S.A.S.; Rahim, E.A.; Embong, Z.; Syahrullail, S. (ScienceDirect, 2018)
This paper studies the applications of modified Jatropha oil-based (MJO) lubricant as potential vegetable-based metalworking fluids, containing additives of two oil-miscible ionic liquids; [P66614][Phosphinate] (PIL) and [N1888][NTf2] (AIL) at 1%, 5%, and 10% weight concentration. The lubricant samples are validated for corrosion, four ball tribology and tapping torque experiments. Using optical microscope, profilometer, AFM, SEM, EDS and XPS analysis, worn surfaces were investigated. The lubrication performance of MJOþAIL10% and MJOþPIL1% samples provide competitive lubrication performance to that other lubricant samples used herein. They have shown improved corrosion inhibition, superior friction reduction, lower worn surface area, excellent surface finish and increased tapping torque efficiency. These superior tribological results correspond to the metal oxide tribofilm formation and anti-corrosion behavior of MJOþAIL10% sample.